Unlocking the Mystery of the Therapeutic Effects of Chinese Medicine on Cancer - Liu, Shao-Hsiang; Chen, Po-Sheng; Huang, Chun-Chieh; Hung, Yi-Tu; Lee, Mei-Ying; Lin, Wei-Hung; Lin, Yuan-Chuan; Lee, Alan Yueh-Luen (Frontiers in Pharmacology, 2021)
Over the past decade, the rise of cancer immunotherapy has coincided with a remarkable breakthrough in cancer therapy, which attracted increased interests in public. The scientific community clearly showed that the emergence of immunotherapy is an inevitable outcome of a holistic approach for cancer treatment. It is well established that traditional Chinese medicine (TCM) utilizes the principle of homeostasis and balance to adjust the healthy status of body. TCM treatment toward cancer has a long history, and the diagnosis and treatment of tumors were discussed in the ancient and classical literatures of Chinese medicine, such as the Yellow Emperor’s Inner Canon. Precious heritage has laid the foundation for the innovation and development of cancer treatment with TCM. The modern study indicated that TCM facilitates the treatment of cancer and enhances the survival rate and life expectancy of patients. However, the pharmacological mechanisms underlying these effects are not yet completely understood. In addition, physicians cannot always explain why the TCM treatment is effective and the mechanism of action cannot be explained in scientific terms. Here, we attempted to provide insights into the development of TCM in the treatment and interpret how TCM practitioners treat cancer through six general principles of TCM by using modern scientific language and terms based on newly discovered evidence.